2014
DOI: 10.1186/1916-0216-43-13
|View full text |Cite
|
Sign up to set email alerts
|

Validation of pharyngeal findings on sleep nasopharyngoscopy in children with snoring/sleep disordered breathing

Abstract: ObjectiveTo validate the pharyngeal findings in sleep nasopharyngoscopy (SNP) of children with snoring - sleep disordered breathing (S-SDB).DesignProspective agreement diagnostic study on retrospective data.MethodsWe conducted an inter-and intra-rater agreement study on video documentations of SNP performed on children (non-syndromic, complex, or operated upon) who presented with S-SDB. The videos featured various pharyngeal findings (normal, collapse, mixed or obstruction). Three ‘non-expert’ raters at variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…A consistent combination of remifentanyl (2–2.5 mcg/ml) and propofol (200–350 mcg/kg/min) was used for maintenance. If an inhalational anesthetic was used for induction, the tidal volume was ensured to be zero prior to performing DISE [ 8 ]. Lignocaine (1%) was used to topically anesthetize the nasal mucosa.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A consistent combination of remifentanyl (2–2.5 mcg/ml) and propofol (200–350 mcg/kg/min) was used for maintenance. If an inhalational anesthetic was used for induction, the tidal volume was ensured to be zero prior to performing DISE [ 8 ]. Lignocaine (1%) was used to topically anesthetize the nasal mucosa.…”
Section: Methodsmentioning
confidence: 99%
“…The scoring system used is summarized in Table 1 . This system has been described in previous studies and has been shown to have good intra- and inter-rater reliability [ 8 , 20 , 34 ]. Nasal septal deviation (NSD) was graded on a 3 point scale (1: absent, 2:<50% compromise of nasal patency, 3:≥50% compromise of nasal patency), and the degree of rhinitis was graded according to a 3 point endoscopic rhinitis score (ERS) (Grade1, no obstruction to either side (mild or no rhinitis); grade 2, obstruction to 1 side; and grade 3, bilateral obstruction) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that because our study involves the subjective evaluations of three different physicians on the degree of upper airway obstruction, there may be inherent inter-observer variation. A recent study by Ramji et al [ 19 ] tested inter- and intra-rater agreement on sixty-one recorded videos of children undergoing a sleep nasopharyngoscopy. The authors concluded that there was validation for this procedure with good inter- and intra-rater agreement.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are two patterns of pharyngeal compromise that may occur in SDB, namely pharyngeal obstruction or collapse, and can be identified on drug induced sleep endoscopy (DISE) or imaging [ 17 , 18 ]. The pharynx may exhibit collapse upon inspiration in concentrically, lateral wall to lateral wall, or at the tongue base level [ 17 ]. The significance and associations related to each type of collapse has neither been studied nor determined to date.…”
Section: Introductionmentioning
confidence: 99%